Strain and ferroelectric polarization influence on perpendicular magnetic anisotropy of CoFe3N/BaTiO3 heterostructure - Zirun Li; Yongmei Zhang; Huanfei Wen; Chengwei Dong (Results in Physics, 2024)
Electric-field control of perpendicular magnetic anisotropy (PMA) in multiferroic heterostructure offers promising application for energy-efficient information storage. This work presents how magnetic anisotropy can be regulated by simultaneously exploiting strain and ferroelectric polarization in CoFe3N/BaTiO3 heterostructure using first-principles calculations. The calculations reveal strain-induced enhancement of PMA depending on the direction of ferroelectric polarization. Through the analysis of spin–orbit Hamiltonian matrix elements, we elucidate that ferroelectric polarization reversal changes the energy level splitting of d orbitals in interfacial Co atom, and compressive strain induces energy level shifting of d orbitals, giving rise to the competed MAE contribution from spin-conservation and spin-flip terms. This work highlights the underlying mechanism for tuning magnetic anisotropy by the modulation of d-orbital shifting and splitting around the Fermi level, and provides valuable insights for energy-efficient spintronic applications.